209 Attainment of low disease activity and remission with atacicept in patients with systemic lupus erythematosus and high disease activity in the phase IIb ADDRESS II study and its long-term extension. (April 2019) - Morand, Eric; T Merrill, Joan; A Isenberg, David; H Kao, Amy; Vazquez-Mateo, Cristina; Wax, Stephen; Chang, Peter; Pudota, Kishore; Aranow, Cynthia; J Wallace, Daniel
Abstract : Background: Low disease activity (LDA) and remission are important goals in the treatment of patients with SLE. 1 2 Lupus Low Disease Activity State (LLDAS) is associated with reduced damage accrual, 2 and has been shown to be a feasible clinical trial endpoint. 3 In patients with high disease activity (HDA; SLEDAI-2K ≥10) enrolled in the ADDRESS II study, atacicept improved SLE responder index (SRI)-6 response rates and flare prevention at Week 24 vs placebo. Atacicept also demonstrated an acceptable safety profile. 4 We present a post-hoc analysis of data from ADDRESS II and its long-term extension, describing 48-week LDA and remission rates in patients with HDA at Screening. Methods: In ADDRESS II, patients were randomized (1:1:1) to weekly subcutaneous atacicept 75 or 150 mg or placebo for 24 weeks. Atacicept-completers continued at the same dose in the extension study, while placebo-treated patients were switched to atacicept 150 mg (placebo/atacicept 150 mg). This post-hoc analysis assessed: LDA (SLEDAI-2K ≤2), LLDAS (SLEDAI-2K ≤4 without major organ activity, no new disease activity vs previous visit, Physician's Global Assessment [PGA] ≤1, prednisone-equivalent ≤7.5 mg/day, and stable immunosuppressants), 2 and remission (clinical SLEDAI-2K=0, PGA <0.5, prednisone ≤5 mg/day), as proposed by the task force on definitions of remission in SLE (DORIS). 1 Results: Of 306 ADDRESS II patients, 158 (51.6%) had HDA at Screening. At Week 24, 42.4% achieved SRI-6, 23.4% attained LDA, 15.8% LLDAS and 10.8% remission. At Week 48, 52.5% achieved SRI-6, 26.6% attained LDA, 19.0% LLDAS and 10.8% remission. Among 83 patients with HDA at Screening who had an SRI-6 response at Week 48, 49.4% (n=41) attained LDA, 34.9% (n=29) LLDAS and 20.5% (n=17) remission. At 48 weeks, LDA, LLDAS and remission rates were higher in patients treated with atacicept 150 mg vs atacicept 75 mg and vs placebo/atacicept 150 mg (figure 1 ). Conclusions: ADDRESS II patients with HDA at Screening who received atacicept 150 mg were more likely to attain LDA, LLDAS and remission at Week 48 than those treated with atacicept 75 mg or placebo/atacicept 150 mg. These endpoints were more stringent and discriminatory than SRI-6, confirming LLDAS, LDA, and remission to be robust and meaningful endpoints for SLE trials. In addition, these data further support future studies of atacicept in SLE. Funding Source(s): Merck KGaA, Darmstadt, Germany References: Van Vollenhoven et al. Ann Rheum Dis 2017. Franklyn et al. Ann Rheum Dis 2016. Morand et al. Ann Rheum Dis 2018. Merrill et al. Arthritis Rheum 2018.